(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This survey research was conducted to find out The Effectiveness of Customer Satisfaction on Selected Fast-Food chains along Fairview, Quezon City: Basis for Recommendation. This research aims to gain knowledge and awareness of the fast-food chain along Fairview Quezon City. The finding shows that customer satisfaction, customer service as well as the drive-thru service got the highest composite mean out of the others, but between the drive-thru and customer service, customer service got the highest weighted mean of 3.42, which is interpreted as Strongly Satisfied. The results show that most of the respondents are pleased with how the crew or staff treated them with kindness and friendliness; through the process of this paper, the researchers were able to see the real problem that occurred in each of the respondents’ situations. There is a need for attention and awareness of the customer if they give better satisfaction to everyone.